The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1620/tjem.2023.j002
|View full text |Cite
|
Sign up to set email alerts
|

Acute Adverse Events at a Mass Vaccination Site after the Third and Fourth COVID-19 Vaccinations in Japan

Abstract: The third and fourth doses of the vaccine against coronavirus disease 2019 (COVID-19) were widely administered in Japan since December 2021. Currently, however, data is scarce regarding acute adverse events with the third and fourth doses. The present study reports the profiles of acute adverse events after the third and fourth COVID-19 vaccine doses, seen at the site of a mass vaccination center in Japan. Between December 2021 and July 2022, 267,515 individuals received the third, and 32,934 received the four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
(37 reference statements)
0
3
0
Order By: Relevance
“…The safety profile of the fourth dose also seems reassuring. Akaishi et al [ 21 ] compared the burden of acute side-effects recorded after receiving four doses of mRNA-based COVID-19 vaccines, and reported that the incidence rates after the third and fourth doses were significantly lower than those seen after the first and second administrations. The authors also found that the risk of developing vasovagal syncope/presyncope was lower after the fourth compared to the third vaccine dose (0.02 vs. 0.09%: p < 0.001), as was the likelihood of developing post-vaccine allergic reactions (0.01 vs. 0.03%; p = 0.010).…”
Section: Discussionmentioning
confidence: 99%
“…The safety profile of the fourth dose also seems reassuring. Akaishi et al [ 21 ] compared the burden of acute side-effects recorded after receiving four doses of mRNA-based COVID-19 vaccines, and reported that the incidence rates after the third and fourth doses were significantly lower than those seen after the first and second administrations. The authors also found that the risk of developing vasovagal syncope/presyncope was lower after the fourth compared to the third vaccine dose (0.02 vs. 0.09%: p < 0.001), as was the likelihood of developing post-vaccine allergic reactions (0.01 vs. 0.03%; p = 0.010).…”
Section: Discussionmentioning
confidence: 99%
“…Allergic reactions were not common in our study (1% after 1st dose; 0% after 2nd dose), and no incidence of anaphylaxis was reported. In the study by Akaishi et al, acute allergic reactions (0.05–0.005%) and anaphylaxis (<0.005%) were also not common after the 3rd and 4th doses of the vaccine [ 15 ]. It provides valuable information that acute allergic reactions are a relatively uncommon adverse event after SARS-CoV-2 vaccination, which is confirmed by other studies as well [ 16 , 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a cohort of 267,515 individuals who received the third and 32,934 individuals who received the fourth COVID-19 vaccine dosage at the vaccination center in Japan, 0.01–0.1% present vasovagal syncope/presyncope ( 126 ). On the other hand, the relationship between long COVID-19 and vaccines remains unclear.…”
Section: Pots and Vaccinationmentioning
confidence: 99%